Effects of display curvature, display zone, and task duration on legibility and visual fatigue during visual search task. (April 2017) - Park, Sungryul; Choi, Donghee; Yi, Jihhyeon; Lee, Songil; Lee, Ja Eun; Choi, Byeonghwa; Lee, Seungbae; Kyung, Gyouhyung
Abstract: This study examined the effects of display curvature (400, 600, 1200 mm, and flat), display zone (5 zones), and task duration (15 and 30 min) on legibility and visual fatigue. Each participant completed two 15-min visual search task sets at each curvature setting. The 600-mm and 1200-mm settings yielded better results than the flat setting in terms of legibility and perceived visual fatigue. Relative to the corresponding centre zone, the outermost zones of the 1200-mm and flat settings showed a decrease of 8%–37% in legibility, whereas those of the flat setting showed an increase of 26%–45% in perceived visual fatigue. Across curvatures, legibility decreased by 2%–8%, whereas perceived visual fatigue increased by 22% during the second task set. The two task sets induced an increase of 102% in the eye complaint score and a decrease of 0.3 Hz in the critical fusion frequency, both of which indicated an increase in visual fatigue. In summary, a curvature of around 600 mm, central display zones, and frequent breaks are recommended to improve legibility and reduce visual fatigue. Highlights: Curvatures of 600 mm and 1200 mm were more legible and less visually fatiguing than a flat display. Legibility decreased by 8%–37% in the outermost zones of the 1200-mm and flat settings. Visual fatigue increased by 26%–45% in the outermost zones of the flat setting. A 30-min visual search task induced visual fatigue. Use of ∼600 mm curvature, avoiding the outer zones, and frequent breaks are advised for VDT tasks.